1999
DOI: 10.1080/07357909909011723
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Routine Postoperative Laboratory Studies in Patients Undergoing Potentially Curative Resection for Adenocarcinoma of the Colon and Rectum

Abstract: In an effort to lower healthcare costs, this study was undertaken to evaluate the utility of routine postoperative (PO) laboratory studies and determine whether abnormalities alter patient (PT) care. This was a retrospective review of 105 PTs undergoing elective curative resection for colorectal cancer. A serum electrolyte and liver panel and a hematologic panel were drawn in all PTs. OF 8749 total laboratory values obtained, 5894 (67%) were normal. Two of these (0.03%) elicited a therapeutic intervention. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…It is possible these abnormal values are simply stress hyperglycemia secondary to undergoing an abdominal operation. Additionally, in the current study, and the study done by Skendaris, 6 intervention for hyperglycemia was rare, which again indicates care that is not cost-effective. A recent study of patients undergoing joint arthroplasty that included patients with a diagnosis of diabetes found, as would be expected, that a preoperative diagnosis of diabetes was the strongest risk factor for an abnormal postoperative glucose 17 .…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…It is possible these abnormal values are simply stress hyperglycemia secondary to undergoing an abdominal operation. Additionally, in the current study, and the study done by Skendaris, 6 intervention for hyperglycemia was rare, which again indicates care that is not cost-effective. A recent study of patients undergoing joint arthroplasty that included patients with a diagnosis of diabetes found, as would be expected, that a preoperative diagnosis of diabetes was the strongest risk factor for an abnormal postoperative glucose 17 .…”
Section: Discussionmentioning
confidence: 47%
“…In 1999, Skenderis et al published their results examining the utility of routine perioperative serum laboratories in a cohort of 105 patients undergoing surgery for colorectal adenocarcinoma. They found that only 1.4% of all postoperative lab tests required an intervention, and they concluded that postoperative laboratory testing should be “streamlined to only those that are necessary, such as postoperative potassium and hemoglobin.” 6 However, it is not clear whether this practice was widely adopted and how it applies in the ERAS era. Despite intense interest in reducing costs in healthcare over the last two decades, this issue had remained largely unstudied until recently, when studies on the utility of routine serum laboratory tests after pelvic reconstructive surgery, 14 spine fusion, 15 and joint arthroplasty 16–18 were published.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators found that, although minor laboratory abnormalities were common postoperatively (12%–67% depending on the test), only a very small subset (0.03%–5.1% depending on the test) triggered an intervention. 16 Overall, those authors reported that serum potassium, hemoglobin, and serum glucose in patients with diabetes were the only values that led to therapeutic decisions. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 16 Overall, those authors reported that serum potassium, hemoglobin, and serum glucose in patients with diabetes were the only values that led to therapeutic decisions. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Ransom et al 13 examined the usefulness of type and screening in women undergoing Cesarean section and found that most transfusions were related to identifiable risk factors. Skenderis et al 14 examined the usefulness of routine postoperative testing in patients undergoing resection for adenocarcinoma of the colon and rectum. Postoperative serum potassium and glucose in addition to hemoglobin measurements were the only values found to affect patient care.…”
Section: Discussionmentioning
confidence: 99%